Models for omni-channel retailing - Zhang, Lina (2020)
Though many retailers have embarked on the omni-channel journey, most of them are grappling with the difficulties of order fulfilment and delivery in an omni-channel environment. As customers have become more demanding regarding delivery flexibility and more intolerant of long delivery waiting times, it is imperative for retailers to revise their supply chains and operational systems to embrace omni-channel and guarantee high customer service levels. The main objective in this thesis is to explore key supply chain management (SCM) decisions faced by retailers in transition to omni-channel and to use quantitative methods to examine some of these decisions. Based on extensive review from both academic studies and the business literature, we present a conceptual map pinpointing critical supply chain and operations decisions. The conceptual map encapsulates the main contextual factors including retailer characteristics, demand characteristics, order characteristics and supplier characteristics.